Nanoformulations can significantly affect pesticide degradation and uptake by earthworms and plants - Fojtová, Dana; Vašíčková, Jana; Grillo, Renato [UNESP]; Bílková, Zuzana; Šimek, Zdeněk; Neuwirthová, Natália; Kah, Melanie; Hofman, Jakub (CSIRO Publishing, 2019)
An increasing number of nanoformulated pesticides (nanopesticides) have been developed in recent years with the aim to improve pesticide efficiencies and reduce their impact on the environment and human health. However, knowledge about their environmental fate and effects is still very limited. This study compares the soil fate and bioaccumulation of four model nanopesticides (chlorpyrifos and tebuconazole loaded on polymeric and lipid nanocarriers) relative to the conventional formulations and pure active ingredients (all added at 0.5 mg kg -1 ) in microcosms containing earthworms Eisenia fetida and lettuce Lactuca sativa in two soils (LUFA 2.1 and 2.4) over a period of four months. The nanoformulations increased the soil half-life of the pesticides by up to 2 times (e.g. chlorpyrifos with lipid nanocarrier and tebuconazole with polymeric nanocarrier in LUFA 2.1), probably as a direct consequence of the slow release of the pesticide from the nanocarriers. Pesticide bioaccumulation in earthworms was often increased for the nanopesticides probably as a result of their enhanced bioavailability. The nanoformulations were also shown to affect the pesticide bioaccumulation in plants, but trends were inconsistent. Overall, the microcosm results demonstrated that nanoformulations can significantly alter the fate and bioavailability of pesticides. However, generalisations were difficult to make as the impacts depended on the type of nanocarrier, pesticide, soil used and time scale. We believe that our study contributes towards the critical mass of case studies needed to enable a judging of the benefits versus risks of nanopesticides.
Keywords: bioaccumulation; bioavailability; chlorpyrifos; environmental fate; lettuce; nanoparticle; nanopesticide; nanostructured lipid carriers; poly-ϵ-caprolactone; soil; tebuconazole